2006
DOI: 10.1093/nar/gkl555
|View full text |Cite
|
Sign up to set email alerts
|

Twin gradients in APOBEC3 edited HIV-1 DNA reflect the dynamics of lentiviral replication

Abstract: The human immunodeficiency virus (HIV) Vif protein blocks incorporation of two host cell cytidine deaminases, APOBEC3F and 3G, into the budding virion. Not surprisingly, on a vif background nascent minus strand DNA can be extensively edited leaving multiple uracil residues. Editing occurs preferentially in the context of TC (GA on the plus strand) and CC (GG) depending on the enzyme. To explore the distribution of APOBEC3F and –3G editing across the genome, a product/substrate ratio (AA + AG)/(GA + GG) was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(138 citation statements)
references
References 34 publications
13
123
1
1
Order By: Relevance
“…The features of processivity and polarity are determined by the CD1 domain of the monomer, thus revealing the overriding importance of the non-catalytic CD1 in the spatial properties of deamination and in imposing an asymmetric catalytic constraint on full-length Apo3G. These properties are responsible for generating 3Ј35Ј deamination gradients on ssDNA in vitro, which correspond to mutational gradients in HIV RNA observed in vivo (16,22,23,51).…”
Section: Discussionmentioning
confidence: 98%
“…The features of processivity and polarity are determined by the CD1 domain of the monomer, thus revealing the overriding importance of the non-catalytic CD1 in the spatial properties of deamination and in imposing an asymmetric catalytic constraint on full-length Apo3G. These properties are responsible for generating 3Ј35Ј deamination gradients on ssDNA in vitro, which correspond to mutational gradients in HIV RNA observed in vivo (16,22,23,51).…”
Section: Discussionmentioning
confidence: 98%
“…4, A, B, E, and F) suggest that in vivo A3G has the potential to catalyze sizable numbers of processive deaminations on (Ϫ)-cDNA within the limited time that it is single-stranded. Notably, in vivo data reveal twin 5Ј 3 3Ј G to A mutational gradients of the HIV-1 genome, which means that deaminations are increasing toward the 5Ј-end of the (Ϫ)-cDNA in two regions marked by reverse transcription primer sites on the (Ϫ)-cDNA (17,18). It has been suggested that the mutational gradients are attributable to the temporal effects of reverse transcription acting in combination with RNase H, so that regions that remain singlestranded over the longest time frame are most susceptible to A3G-catalyzed deaminations (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Directional deamination is an intrinsic property of A3G, occurring in the absence of an obvious source of energy (e.g. ATP or GTP) (15) and can in principle contribute to the HIV-1 G 3 A mutational bias, increasing in a 3Ј-direction in the RNA genome (17,18). A3G processivity appears consistent with a three-dimensional facilitated diffusion process involving sliding and jumping motions along the DNA (15), where jumping involves microscopic dissociation and reassociation events occurring with the same DNA molecule, rather than diffusion into the surrounding bulk solution (19 -21).…”
Section: Apobec3g (A3g) Restricts Hiv-1 Infection By Catalyzingmentioning
confidence: 99%
“…The env region was chosen for analyses because several studies have confirmed that A3 exhibits a pronounced 59 to 39 editing gradient, resulting in a particular susceptibility to A3 cytidine deaminase activity (38,39). Sixty different clones were sequenced, and the total numbers of bp investigated were 51,000.…”
Section: Peg Ifn-a2b Induces G-to-a Hypermutation In Mddcs Infected Wmentioning
confidence: 99%